China's Revenge Politics Against USA Taxes - Arifani, Devina; Natsir Wong, Liliana (Law Development Journal, 2025)
In 2025, the United States will again implement a new tariff policy on a number of strategic commodities from the People's Republic of China (China), as part of efforts to protect domestic industries and limit China's technological dominance in the global market. The tariffs cover the electric vehicle, semiconductor, solar panel, and strategic metal sectors, with additional tariffs reaching 35%. The US government argues that this policy is intended to respond to unfair trade practices and threats to national security. However, this action is viewed by the Chinese government as a form of economic aggression and a trigger for ongoing bilateral tensions. In response, China launched a policy of revenge in the form of retaliatory tariffs that are measured and strategic. China targets American agricultural products, including soybeans, corn, and beef—sectors that have a direct impact on the US government's political support base. In addition, China has also tightened regulations on American technology companies operating in its territory, and accelerated import substitution programs in national strategic industries. The economic retaliation between the two superpowers has put significant pressure on the global economy. Market uncertainty has increased, foreign investment has slowed, and there have been disruptions in international supply chains, especially in the technology and renewable energy sectors. Developing countries have also been affected by commodity price fluctuations and declining export demand. This tariff conflict shows a shift in international trade patterns from the principles of liberalism to geopolitically based strategic protectionism. This study aims to comprehensively analyze the dynamics of US tariff policy in 2025, the form of China's revenge politics, and its impact on global economic stability in the context of contemporary international political economy.